Analisis Pengaruh Parameter Pemotongan Terhadap Konsumsi Energi Listrik Pada Proses Pembubutan - Asmeati Asmeati; Yanti Yanti (Politeknik Negeri Ujung Pandang, 2015)
This research is focused on determining the consumption of electrical energy in machining process. In this study, the calculation and measurement used to evaluate the needs of electrical energy for machining process. The research conducted on low carbon steel and the condition of machining in particularly the turning process. This allows the definition of energy distribution for machining process and the identification of the main focus areas to reduce the energy used for the machine. This methodology includes the preparation of materials and tools, measure the energy on a lathe and machine the process performance. Experimental results will be retrieved amount of electrical energy consumption used in turning process that can be performed by direct measurement and calculation. Thus, it can then be analyzed by Analysis of Variance using a Design Expert to get optimum cutting conditions with regard to the criteria of minimum energy.